HUBUNGAN KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DENGAN KEPUASAN KERJA GURU PAUD DI PAMIJAHAN KABUPATEN BOGOR - Hartati, Sri; Trimulyo, Joko; Hasanah, Tita (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
Teacher job satisfaction requires special attention, because of its impact on organizational goals. Each teacher has different job satisfaction due to differences in individual characteristics and needs. Good, polite, gentle, and supportive interpersonal communication in a warm atmosphere can provide valuable input for evaluating personal, group, and organizational development. This study aims to determine the relationship between the principal's interpersonal communication and teacher job satisfaction. This type of research is quantitative and was conducted in Pamijahan District, Bogor Regency. The respondents of the study were 94 PAUD teachers selected using random sampling techniques. The data obtained were analyzed using quantitative descriptive and inferential statistics. The results of the study showed that the average score of the principal's interpersonal communication and teacher job satisfaction was in the very good category. In addition, the correlation test produced a Sig value of 0.018 and a Pearson Correlation of 0.243, which indicated a positive but weak relationship between the principal's interpersonal communication and teacher job satisfaction. This indicates that although the principal's interpersonal communication plays a role in teacher job satisfaction, there are other factors that also have an influence.